Power Point Application Skills need of Library and Information Science students for job performance in public services in Imo State, Nigeria - Dr. Okpokwasili Nonyelum P. (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
This study sought to determine the power-point application skills need and Library science and information students for job performance in public service in Imo State. The purpose of this study was to determine the PowerPoint application skills need of library science and information students for job performance in public service in Imo State. A research question and a null hypothesis were formulated to guide the study. A descriptive survey research design was adopted for the study. The population comprised 1,200 Library and information science students and lecturers with sample size of 360 (310 students and 56 lecturers) respondents selected using stratified random sampling from higher institutions of learning in Imo State. A structured and validated instrument titled “PowerPoint Application Skills need and Library and Information science students and lecturers’ performance in the public service in Imo State. (POPSNLAISL)” was used to elicit data for the study. Cronbach Alpha procedure was used to establish the reliability of the instrument with a coefficient of 0.76 which showed that the instrument was reliable. Mean and Improvement Need Index (INI) were used to analyze the responses from the research question, while the null hypothesis was tested using the independent t-test at 0.05 level of significance. The result showed that PowerPoint application skills of Library and Information science Lecturers are highly needed with positive improvement index. The following recommendations were given amongst others: that Library and Information science students should be given awareness by their employers on the need to acquire PowerPoint application skills.